THE IMPACT OF THE IMPLEMENTATION OF TEMPORARY IMPORT PROCEDURE ON ELECTRONIC PRODUCTS: INPUT–OUTPUT ANALYSIS - Hadi, Dedi Abdul; Matsumoto, Toru (UI Scholars Hub, 2018)
Currently, imported electronic products enter the Indonesian market using general import procedures, where the importer has to pay the import duty and taxes in full rate. In the absence of proper recycling systems, the electronic products that have reached their end of life and those are no longer used, end up in the landfills. Some researchers found hazardous materials inside the electronic products that could contaminate water, soil and air. Therefore, another strategy is needed to avoid negative effects on the environment. The Temporary import policy is one of the import procedures under Customs administration control, which states that goods can only be imported for a specific period, and should be re-exported afterwards. This paper tries to analyze the impact of the implementation of the temporary import policy on electronic products. By employing the Input-Output Analysis to the data from the Statistic Central Bureau and Indonesian Customs, this paper identified the impacts of the proposed procedure to some sectors in the Indonesian input-output table, namely: import activity, waste management and recycling system, transportation and storage, and final demand. The result shows increasing in quantity to be re-exported, and potential benefit from transportation and warehousing, leasing and rental services, and other business.